A method for scoring 4-nitroquinoline 1-oxide-induced murine esophageal squamous neoplasia. Issue 3 (May 2023) - Aziz, Zaryab; Washington, Mary Kay; Jacobse, Justin; Choksi, Yash
A mouse model for esophageal squamous cell carcinoma (ESCC) is induced by oral administration of the carcinogen 4-nitroquinoline 1-oxide (4-NQO). There is not an objective method for determining histopathologic severity of disease in this model. We aim to create a clearly defined and easily applied scoring system that can quantify the severity of 4-NQO-induced murine ESCC. Fifteen wild-type C57BL/6J mice were treated with 4-NQO for 8 (n = 8) or 16 (n = 7) weeks, while the rest (n = 9) were treated with vehicle, as 8 weeks of 4-NQO typically results in dysplasia and 16 weeks in carcinoma. We identified histologic abnormalities of the esophagus in this model and developed metrics to grade severity of dysplasia, papillomas, and invasion. Scores were then calculated using quantitative digitized image analysis for measuring depth and extent of each feature within the entire sample. Each feature was also assigned a weight based on its relation to cancer severity. Histology scores were significantly different in the three groups, suggesting that this method can discriminate dysplasia from carcinoma. This model can be applied to any mouse treated with 4-NQO.